Folate Carrier Deficiency Drives Differential Methylation and Enhanced Cellular Potency in the Neural Plate Border - Alata Jimenez, Nagif; Strobl-Mazzulla, Pablo H. (Frontiers in Cell and Developmental Biology, 2022)
The neural plate border (NPB) of vertebrate embryos segregates from the neural and epidermal regions, and it is comprised of an intermingled group of multipotent progenitor cells. Folate is the precursor of S-adenosylmethionine- the main methyl donor for DNA methylation- and it is critical for embryonic development, including the specification of progenitors which reside in the NPB. Despite the fact that several intersecting signals involved in the specification and territorial restriction of NPB cells are known; the role of epigenetics - particularly DNA methylation- has been a matter of debate. Here, we examined the temporal and spatial distribution of the methyl source, analyzed the abundance of 5mC/5hmC and their epigenetic writers throughout the segregation of the neural and NPB territories. Reduced representation bisulfite sequencing (RRBS) on Reduced Folate Carrier 1 (RFC1) deficient embryos leads to the identification of differentially methylated regions (DMRs). In RFC1-deficient embryos, we identified several DMRs in the Notch1 locus, and the spatiotemporal expression of Notch1, and its downstream target gene Bmp4, were expanded in the NPB. Cell fate analysis on folate deficient embryos revealed a significant increase in the number of cells co-expressing both neural (SOX2) and NPB (PAX7) markers, which may represent an enhancing in the cellular potential of those progenitors. Taken together, our findings propose a model where the RFC1 deficiency drives methylation changes in specific genomic regions that correlated with a dysregulation of pathways involved in early development such as Notch1 and BMP4 signaling. These changes affect the potency of the progenitors residing in the juncture of the neural plate and NPB territories, thus driving them to a primed state.